LGG-47. Single-cell RNA Sequencing Reveals Immunosuppressive Myeloid Cell Diversity During Malignant Progression in Glioma. (3rd June 2022) - Rajendran, Sakthi; Peterson, Clayton; Canella, Alessandro; Hu, Yang; Gross, Amy; Cam, Maren; Serin-Harmanci, Akdes; Distefano, Rosario; Nigita, Giovanni; Wang, Wesley; Hester, Mark; Miller, Katherine; et al.
Abstract: Myeloid cells and macrophages have been shown to promote immunosuppression in high-grade gliomas (HGG), however their roles in malignant progression of low-grade glioma (LGG) are poorly understood. Here, we investigated the heterogeneity of the immune microenvironment during glioma progression using a murine model that recapitulates the malignant progression of low to high-grade glioma. To that end, we performed single-cell RNA sequencing on CD45+ immune cells isolated from animals bearing no tumor (NT), LGG, and HGG. We observed an increased infiltration of CD4+ T cells, CD8+ T cells, B cells, and natural killer cells in the tumor microenvironment of LGG, whereas this infiltration was abrogated in HGG. Our study identified two distinct macrophage clusters across all 3 samples, with signatures of bone marrow derived and resident macrophages, respectively. These macrophages showed an immune-activated phenotype (Stat1, Tnf, Cxcl9 and Cxcl10 ) in LGG, but then evolved to a more immunosuppressive state ( Lgals3, Apoc1 and Id2 ) in HGG, restricting T cell recruitment and activation. In addition, we identified CD74 and macrophage migration inhibition factor (MIF) as potential targets for both these distinct macrophage populations, based on their increased expression in LGG and HGG compared to NT. Targeting these factors during the LGG therapeutic window may inhibit myeloid cells and intra-tumoral macrophages and attenuate their immunosuppressive properties and impair malignant progression.